2005
DOI: 10.1111/j.1460-9592.2004.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of caudal catheter position in infants

Abstract: The positioning of caudally inserted epidural catheters is crucial to their effectiveness. However, level assessment can be difficult and time consuming. We report the use of ultrasound to assess the catheter position in three patients aged between 1 and 10 months. The advantages and disadvantages of this technique are discussed in relation to other methods of assessing caudal catheter placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 8 publications
0
25
0
1
Order By: Relevance
“…Current research supports the use of ultrasound imaging in both the transverse (Raghunathan et al, 2008;Schwartz et al, 2008) and longitudinal (Roberts & Galvez, 2005;Park et al, 2006) planes to guide needle placement during a caudal block. For the transverse technique, the probe was placed just cephalad to the point of injection.…”
Section: Techniquementioning
confidence: 56%
See 2 more Smart Citations
“…Current research supports the use of ultrasound imaging in both the transverse (Raghunathan et al, 2008;Schwartz et al, 2008) and longitudinal (Roberts & Galvez, 2005;Park et al, 2006) planes to guide needle placement during a caudal block. For the transverse technique, the probe was placed just cephalad to the point of injection.…”
Section: Techniquementioning
confidence: 56%
“…The ligament can be identified as a thick, linear, hyperechoic band that slopes caudally. When ossification has occurred at the midline, as is the case in older children, the paramedial longitudinal view is optimal because it allows the ultrasound beam to penetrate the spaces lateral to the spinous processes (Roberts & Galvez, 2005).…”
Section: Outcome and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This imaging was performed after the block procedure rather than during insertion. Another study (64) concluded that one month of age was the threshold for clear catheter tip visibility, although only three children were studied (one, eight and 10 months of age). These studies used catheters without much echogenic property; the use of metal-coiled catheters, which appear bright with striated features, may circumvent this deficiency (65).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…While this action obviates the need for a second procedure, it is not optimal if a high sensory level is needed. Entrance into the caudal/epidural space is confirmed by transverse ultrasonography [8][9][10][11]. Ultrasound is also helpful in determining epidural catheter tip position, which is essential in achieving dermatome-specific analgesia.…”
mentioning
confidence: 99%